Exploration of the atomic-level structures of the icosahedral clusters in Cu–Zr–Al ternary metallic glasses via first-principles theory - Wenfei Lu; Zhilue Wang; Hongping Xiang; Aihan Feng; Jun Shen (Materials Research Express, 2022)
The atomic-level structures of the icosahedral clusters in Cu–Zr–Al ternary metallic glasses were studied via the first-principles theory. The rules of icosahedra stability were determined. Icosahedra with a better chemical order or with a better symmetry exhibited a better stability. The strong connectivity between Al atom and Cu and Zr atoms was observed as demonstrated by the obvious degree of ‘bond shortening’. The Al atom contributed more to the structural stability when used as the central atom than the other atoms. Therefore, the addition of even a small amount of Al atom to the Cu–Zr binary system remarkably improved the stability of the icosahedron structures. The continued addition of Al atoms had a lower contribution to the improvement to the glass-forming ability of the Cu–Zr–Al alloys.